ADVANTAGES AND DISADVANTAGES OF SHAREHOLDERS AND A SUPERVISORY BOARD (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This topic analyzes the importance of the role of shareholders and the supervisory board in the management of corporations. The proper use of shareholders' voting rights allows the supervisory board to improve corporate governance by monitoring management, and their accountability is also important in the management of corporations. The independence and impartiality of the supervisory board are shown to be important in increasing the transparency and accountability of company management.